BIOGAS AND CH4 QUALITY AND PRODUCTIVITY BY CO-DIGESTING DROMEDARY DUNG WITH KITCHEN WASTE AND SEWAGE SLUDGE WATER UNDER MESOPHILIC CONDITIONS - Benaissa, K.; Dadamoussa, B.; Bendraoua, A. (University of Eloued جامعة الوادي, 2017)
Five laboratory-scale studies were set-up to investigate the effects of dromedary dung (DD) co-digestion with kitchen waste (KW) and sewage sludge water (SSW) at five ratios, under mesophilic conditions (31-35Â°C) by examining operation stability, CH4 and biogas production potentials. The result obtained showed that KWDDSSW produced the highest CH4 content (64.51%), followed by DDSSW (51.37%) and DDKW (34.77%). The daily CH4 production was linearly correlated with pH, high volatile solids and COD degradation in the feedstock, indicating methane production was probably associated with higher supply of organic carbon source that favored the growth of active biomass. KWDDSSW and DDSSW were favored in terms of volume of flammable gas production of biogas and flamed on the 8th day. This study is being the first attempt on CH4 production of combined wastes with DD of Algeria.
Articale in Journal of fundamental and Applied Sciences Vol. 09, N. 03
Keywords: Anaerobic co-digestion; biogas; methane; mesophilic conditions; kitchen waste; dromedary dung; sewage sludge water